Characteristics of molecular classification in 52 endometrial cancer and atypical hyperplasia patients receiving fertility-sparing treatment - Yiqin Wang; Nan Kang; Liwei Li; Zhiqi Wang; Rong Zhou; Danhua Shen; Jianliu Wang (BMJ Publishing Group, 2023)
Objective: To investigate the molecular classification of endometrial cancer (EC) and atypical endometrial hyperplasia (AEH) patients treated with fertility-sparing treatment (FST), and its relationship with clinicopathological factors and treatment efficacy. Methods: A total of 52 ​EC and AEH patients who received FST and molecular classification tested by next generation sequencing in Peking University People's Hospital from June 2020 to December 2022, were retrospectively collected. We analyzed the relationship between molecular classification and clinicopathological factors and treatment outcomes. Results: (1) Of the 52 patients, including 46 ​EC and 6 AEH patients, 42 (80.8%) achieved complete remission (CR) after FST, with a median time to achieve CR of 9 months. Ten cases (23.8%) had recurrence. (2) Patients were distributed into 4 molecular subgroups as 39 cases (75%) of copy number low (CNL) , 7 cases (13.5%) of microsatellite instability-high (MSI-H) , 4 cases (7.7%) of POLE mutations (POLEmut), and 2 cases (3.8%) of copy number high (CNH). Patients with MSI-H subgroup had more family history of tumor (6/7), more with loss of expression of mismatch repair (MMR) protein (7/7), and higher expression level of Ki-67 (3/3). (3) Patients with MSI-H subgroup had the lowest CR rate at 6 months (0/7, P ​= ​0.014), and survival analysis showed that such patients were less likely to achieve CR than those with CNL (P ​= ​0.022). For CNL patients, median 6-month CR rate was 40.6%. In addition, CR was obtained in 3 (3/4) POLEmut patients and 2 (2/2) CNH patients, respectively. Conclusions: Molecular classification relates with the treatment response in patients with EC and AEH receiving FST. Patients with MSI-H subgroup have poor treatment efficacy, and patients with CNL need to be further divided to predict treatment benefit. There are also a few successful cases in POLEmut and CNH subtgroups, which needs further research.